Spiritual Culture Formation of Young Teachers in the System of Higher Education: The Way for Social Maturity Development - Asetova, Zhannur; Abildina, Saltanat; Anesova, Albina Zh.; Kystaubayeva, Zaure; Ryskeldina, Anar (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
The formation of spiritual culture should be based on the principles that guide every teacher in the implementation of their pedagogical skills in direct learning. The purpose of our study is to substantiate that young teachers’ social maturity is characterized not only by the level of knowledge, development of their orientations but also by the degree of personal spiritual culture. We have applied the method of diagnosing a level of young teacher’s social maturity development as a moderator in the search for spiritual values, but also a participant in the formation of personal spiritual culture directly at the student himself. Diagnostic sections have shown that the index of general social maturity of young teachers who shape the spiritual culture of students, is growing much faster compared to the young teachers who didn’t show the activity of this kind. From the experimental data, it follows that young teachers’ activity in creating a pedagogical environment of their school is an effective factor in the intensification of their social maturity formation. Investigating the problem of the formation of social maturity of the individual, a certain system of personal orientations develops, which serves as the basis of spiritual culture, which the student can choose. The authors show that such an opportunity can only be implemented with the teacher’s integrated participation as a carrier of moral values. The study’s novelty is determined by the fact that each of the participants in the educational process seeks to realize the share and type of moral views for the fulfillment of their personal interests. The study’s practical significance is determined by the fact that spiritual culture can be based not only on its private but also on its public perception.